The Development of Students’ Self-Regulated Learning Through Online Learning Design - Dina Mardiana; Umiarso El-Rumi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2021)
AbstractSelf-regulated learning is one of the most important factors in online education. This research focused on exploring how the learning design of an online Islamic education course called Pendidikan Agama Islam (PAI) facilitated the development of students’ self-regulated learning. This study was situated at the State University of Malang (MUs), Indonesia and used qualitative approach in the form of case study as its methodology. The data were collected through documentation, online-based interviews, and observation. After being collected, the data then were analyzed using the interactive model of Miles, Huberman, and Saldana. The research found that the PAI course at State University of Malang (MUs) had four learning design stages consisting of stimulation and problem identification, learning problem-content analysis, verification of results, and generalization. This stages facilitated the development of students’ self-regulated learning, as observed through three indicators owned by each student, namely, creativity, ability to think critically, and self-regulation. The implication of this study is the emerge of the technical-didactic side of online Islamic education learning through a designed learning design stages so that in the end it will lead to benefits in achieving educational goals more effectively.AbstrakPembelajaran mandiri merupakan salah satu faktor terpenting dalam pembelajaran online. Penelitian ini berfokus pada eksplorasi tentang bagaimana desain pembelajaran daring matakuliah pendidikan Islam yang disebut Pendidikan Agama Islam (PAI) memfasilitasi pengembangan pembelajaran mandiri mahasiswa. Penelitian ini berlokasi di Universitas Negeri Malang (MUs), Indonesia dan menggunakan pendekatan kualitatif berupa studi kasus sebagai metodologinya. Data dikumpulkan melalui dokumentasi, wawancara berbasis online, dan observasi. Setelah dikumpulkan, data kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Penelitian menemukan bahwa matakuliah PAI di Universitas Negeri Malang (MUs) memiliki empat tahap desain pembelajaran yang terdiri dari stimulasi dan identifikasi masalah, analisis konten masalah pembelajaran, verifikasi hasil, dan generalisasi. Tahapan ini memfasilitasi pengembangan pembelajaran mandiri mahasiswa, sebagaimana terlihat melalui tiga indikator yang dimiliki oleh masing-masing mahasiswa, yaitu, kreativitas, kemampuan berpikir kritis, dan regulasi diri. Implikasi dari penelitian ini adalah munculnya sisi teknis pembelajaran daring Pendidikan Agama Islam melalui tahapan desain pembelajaran yang dirancang sehingga pada akhirnya akan bermanfaat dalam mencapai tujuan pendidikan secara lebih efektif. How to Cite: Mardiana, D, Umiarso. (2021). The Development of Students’ Self-Regulated Learning Through Online Learning Design. TARBIYA: Journal of Education in Muslim Society, 8(2), 119-134. doi:10.15408/tjems.v8i2.22804.